Experience with Hepatitis B Viral load Testing in Jharkhand - Sana Irfan; Mahua Das Gupta; NP Sahu; Zulfiquar Ali Bhuttoo; Poonam Kumari (Archives of Hepatitis Research - Peertechz Publications, 2019)
Background: Quantification of the viral burden is an important laboratory tool in the management of hepatitis B virus (HBV)-infected patients. However, widespread use of assays is still hampered by the high cost. Treatment reduces viral load to undetectable levels. HBV infected patients tend to have high HBV DNA levels, and severe liver disease.  Objectives: This study was carried out to determine the pattern of HBV viral load levels of patients in Jharkhand.  Method: Variables included socio demographics like age, sex, occupation, history of vaccination, surgery, IVDU.etc. The COBAS Amplicor automated Analyzer (PCR based) was used to assay the virus quantitatively.  Results: 366 number of patients were tested from 2013 to 2015. HBV viral titre ranged between. <6 IU/ml to>1.1 × 108. Conclusion: There was a high occurrence of viral titre as well as suspected core mutants in the population studied. Viral load is a risk factor for cirrhosis and hepatocellular carcinoma. A policy earmarked to combat this virus in Jharkhand is hereby solicited.